Cannabinoid modulation of opioid analgesia and subjective drug effects in healthy humans - Babalonis, Shanna; Lofwall, Michelle R.; Sloan, Paul A.; Nuzzo, Paul A.; Fanucchi, Laura C.; Walsh, Sharon L. (Psychopharmacology, 2019)
Rationale Dozens of preclinical studies have reported cannabinoid agonist potentiation of the analgesic effects of μ-opioid agonists. Objectives The aim of this study was to determine if a cannabinoid agonist could potentiate opioid analgesia in humans using several laboratory pain models. Methods Healthy participants ( n = 10) with/out current drug use/pain conditions completed this within-subject, double-blind, placebo-controlled, randomized outpatient study. Nine 8-h sessions were completed during which dronabinol (0, 2.5, 5 mg, p.o.) was administered 1 h before oxycodone (0, 5, 10 mg, p.o.) for a total of 9 test conditions. Outcomes included sensory threshold and tolerance from four experimental pain models (cold pressor, pressure algometer, hot thermode, cold hyperalgesia), along with participant- and observer-rated, performance and physiological effects. Results Oxycodone produced miosis ( p < 0.05) and analgesic responses (e.g., pressure algometer [ p < 0.05]), while dronabinol did not ( p > 0.05). Depending on the dose combination, dronabinol attenuated or did not alter oxycodone analgesia; for example, dronabinol (2.5 mg) decreased the analgesic effects of oxycodone (10 mg) on pressure tolerance. Conversely, dronabinol increased oxycodone subjective effects (e.g., drug liking) ( p < 0.05); oxycodone (5 mg) ratings of “high” were potentiated by 5 mg dronabinol ( p < 0.05; placebo = 1.1 [± 0.7]; 5 mg oxycodone = 4.7 [± 2.2]; 5 mg dronabinol = 9.9 [± 8.4]; 5 mg oxycodone + 5 mg dronabinol = 37.4 [± 11.3]). Conclusions This study indicates that dronabinol did not enhance the analgesic effects of oxycodone and increased abuse- and impairment-related subjective effects. These data suggest that dronabinol may not be an effective or appropriate opioid adjuvant; it could potentially increase opioid dose requirements, while increasing psychoactive opioid effects.